Implementation of music in government preschools in Malaysia: music activities, teachers' perceptions and teachers' self-efficacy. - Chan, Cheong Jan; Kwan, Shwu Shyan (Universiti Putra Malaysia Press, 2010)
In this paper, the implementation of music in government preschools is studied from three aspects, namely music activities, teachers' perception of the role of music in preschool education, and teachers' self efficacy in music teaching. A questionnaire, which was designed according to the local curriculum syllabus, as well as adapted parts of Wu's (1999) and Oreck's (2001) research instruments, was distributed to 138 preschool teachers in various districts in the state of Selangor, from which 96 valid responses were gathered. The findings revealed that the music activities carried out in preschool, from the order of the most frequently conducted, are group singing, music and movement, listening, sound exploration, and instrument playing. Meanwhile, 95.8% of the respondents conducted group singing daily, and only 28.1% conducted music and movement daily. More than 70% seldom or had never conducted sound exploration activities. Majority of the respondents perceived that music plays a role in personal and social development, music skills and knowledge development, classroom management, and other benefits. There are however disagreements by few on the aspects related to the importance of music in child development. The findings on teachers' self efficacy revealed that one-third of the respondents were not confident to conduct music activities in school. These findings reflected the background of the respondents, whereby 31.3% were untrained in preschool education and 92.7% others did not possess any relevant qualification for instrumental proficiency.